Semi-quantitative reconstruction of early to late Holocene spring and summer sea ice conditions in the northern Barents Sea - Berben, Sarah Miche Patricia; Husum, Katrine; Navarro-Rodriguez, Alba; Belt, Simon T.; Sørensen, Steffen Aagaard (Journal of Quaternary Science, 2017)
Accepted manuscript version. Published version available at: http://doi.org/10.1002/jqs.2953 Semi-quantitative estimates of early to late Holocene spring sea ice concentration (SpSIC) andoccurrence of summer sea ice for the northern Barents Sea have been obtained by analysing the biomarkers IP 25 ,brassicasterol and a tri-unsaturated highly branched isoprenoid lipid in a Holocene marine sediment core.Sub-surface water mass variations were derived from planktic foraminiferal assemblages and stable isotopes (d 18 O,d 13 C). The record indicates paleoceanographic changes over three intervals. During Period I (ca. 9500–5900 cal aBP), the study location experienced the lowest recorded SpSIC (ca. 25%) with short spring seasons and longproductive summers, resulting partly from increased Atlantic Water inﬂow that caused a stronger ocean–atmosphere heat exchange. Throughout Period II (ca. 5900–2700 cal a BP), the winter sea ice margin migratedsouthwards and an overall cooling trend resulted in higher SpSIC (ca. 60%) and increased delivery of cold ArcticWater. During Period III (ca. 2700 cal a BP to present), SpSIC increased further (ca. 75%) and some sea iceremained during summer months. A sub-surface warming probably indicates a decoupling of heat exchangebetween the ocean and the atmosphere. Longer springs and shorter summers were accompanied by the mostsoutherly location of the winter sea ice margin.